Labor Union Membership and Life Satisfaction in the United States. (June 2016) - Flavin, Patrick; Shufeldt, Gregory
While a voluminous literature examines the effects of organized labor on workers' wage and benefit levels in the United States, there has been little investigation into whether membership in a labor union directly contributes to a higher quality of life. In this paper, we uncover evidence that union members are more satisfied with their lives than those who are not members and that the substantive effect of union membership on life satisfaction rivals other common predictors of quality of life. Moreover, we find that union membership boosts life satisfaction across demographic groups regardless if someone is rich or poor, male or female, or young or old. These results suggest that organized labor in the United States can have significant implications for the quality of life that citizens experience.